2021
DOI: 10.4018/jgim.2021010103
|View full text |Cite
|
Sign up to set email alerts
|

A Perception-Based Model for Mobile Commerce Adoption in Vietnamese Small and Medium-Sized Enterprises

Abstract: This paper investigates the critical determinants for the adoption of mobile commerce (m-commerce) in Vietnamese small and medium-sized enterprises (SMEs) from the perspective of managers. A perception-based conceptual model is developed with respect to the technology-organization-environment framework. The conceptual model is then tested and validated using structural equation modelling on the data collected from 513 SMEs in Vietnam. The study shows that perceived benefits, perceived compatibility, perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 90 publications
(175 reference statements)
0
7
0
Order By: Relevance
“…Chau and others believe that, without taking corporate tax into account, first of all, the size of an enterprise's debt will not affect the value of the enterprise; that is, the financing structure of the enterprise has nothing to do with the value of the enterprise. Secondly, the cost of equity of a debtburdened company is the sum of the cost of equity of a non-debt-burdened company with the same risk and the risk premium, and the risk premium is also determined by the cost of equity, debt financing cost, and risk premium of a non-debt-burdened company; the proportion of property rights of the enterprise is determined [4]. Jwo et al believe that if personal income tax is taken into account, the interest expenses incurred by enterprises due to debt financing will be deducted from the total tax payment, and the effect of the increase in enterprise value will be reduced, and the tax shield of debt will be reduced; the effect is not so obvious [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chau and others believe that, without taking corporate tax into account, first of all, the size of an enterprise's debt will not affect the value of the enterprise; that is, the financing structure of the enterprise has nothing to do with the value of the enterprise. Secondly, the cost of equity of a debtburdened company is the sum of the cost of equity of a non-debt-burdened company with the same risk and the risk premium, and the risk premium is also determined by the cost of equity, debt financing cost, and risk premium of a non-debt-burdened company; the proportion of property rights of the enterprise is determined [4]. Jwo et al believe that if personal income tax is taken into account, the interest expenses incurred by enterprises due to debt financing will be deducted from the total tax payment, and the effect of the increase in enterprise value will be reduced, and the tax shield of debt will be reduced; the effect is not so obvious [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior studies failed to address how low-income earners such as artisans in developing countries are using a wide range of sophisticated mobile devices such as smartphones and tablets for mobile online shopping and buying, as well as for making payments in physical locations (Chau et al, 2021;Faqih & Jaradat, 2015;Pipitwanichakarn & Wongtada, 2020;Tuffour et al, 2018). Secondly, despite Ghana having the world's third-highest mobile phone penetration rate, behind China and Kenya, and being named the fastest-growing mobile money market in Africa by the World Bank over the last five years (Collins, 2021;Ngila, 2021), there is little empirical research on mobile commerce adoption compared to other jurisdictions.…”
Section: Introductionmentioning
confidence: 99%
“…It, therefore, implies that the adoption of m-commerce requires the formulation of networks, coordination with other partners and importantly, sharing of resources with the intent of satisfying the needs of diverse and ever-changing customers of the contemporary technology-driven time (Ghobakhloo et al , 2011). Chau (2021) also found that pressures from customers are essential to adopting m-commerce by the SMEs as such adoption would make the customers feel that their service providers meet their requirements for maintaining a good relationship and possessing the fitness to do business together.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…This position has been established by Gangwar et al (2015), who suggested that one of the major pushing factors forcing organizations to adopt IS/IT is competitive pressure. Likewise, Chau et al (2021) argue that SMEs would come under pressure to adopt m-commerce to compete when their competitors have equally adopted similar technologies. Previous empirical studies report a positive and significant relationship between competitive pressure and adoption and diffusion of IT adoption (Alrawabdeh, 2014) such as m-commerce.…”
Section: Pressure From Competitorsmentioning
confidence: 99%